A Triangular Conflict: The Nyasaland Protectorate and Two Missions, 1915–33 - Thompson, David Michael (Studies in church history, 2018)
The idea that the churches became agents of empire through their missionary activity is very popular, but it is too simple. Established Churches, such as those of England and Scotland, could certainly be used by government, usually willingly; so could the Roman Catholic Church in the empires of other countries. But the position of the smaller churches, usually with no settler community behind them, was different. This study examines the effects of the Chilembwe Rising of 1915 on the British Churches of Christ mission in Nyasaland (modern Malawi). What is empire? The Colonial Office and the local administration might view a situation in different ways. Their decisions could thus divide native Christians from the UK, and even cause division in the UK church itself, as well as strengthening divisions on the mission field between different churches. Thus, even in the churches, imperial actions could foster the African desire for independence of empire.